Towards Efficient and Secure Access Control System for Mobile Cloud Computing - Tu, Shanshan; Huang, Yongfeng (China communications, 2015)
This paper proposes a new access architecture onmobile cloud,which introduces a middle layer sitting between mobile devices and their cloud infrastructure.This middle layer is composed of cloudlets which are deployed by cloud services providers,such as wireless network access points（APs）,to improve the performance of mobile cloud servicesand be different from traditional mobile operator mode.Then based on this new architecture.we improve our previous（Attribute-basedencryption） ABE access control scheme on cloud for mobile cloud,which is proposed to offload the main amount of computations to the cloudlet as the function of cloud.Simulationresults demonstratethe new access control scheme takes into consideration response time constraints and network statusof access task execution,while satisfying certain network security for mobile cloud.